TRADISI RESEPSI AL-QUR'AN DI MASYARAKAT GEMAWANG SINDUADI MLATI YOGYAKARTA: (Kajian Living Qur'an) - M.Ulil Abshor (Institut Agama Islam Negeri (IAIN) Keiri, 2019)
Islam springing of the Qur'an is understood as an ideology that gives birth to behavior in the social tradition of society. Likewise the meaning of giving birth exegesis (social interpretation). understanding and meaning of the Qur'an is called